2020
DOI: 10.1016/j.omtm.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Hematopoietic Stem Cell Gene Therapy Rescues Clinical Phenotypes in a Murine Model of Pompe Disease

Abstract: Pompe disease is a lysosomal storage disorder caused by malfunctions of the acid alpha-glucosidase (GAA) enzyme with a consequent toxic accumulation of glycogen in cells. Muscle wasting and hypertrophic cardiomyopathy are the most common clinical signs that can lead to cardiac and respiratory failure within the first year of age in the more severe infantile forms. Currently available treatments have significant limitations and are not curative, highlighting a need for the development of alternative therapies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 69 publications
3
10
0
3
Order By: Relevance
“…Interestingly, in our study, although GAA enzyme activity was detectable in the brain of mice in the GAAco group at approximately 11% and 30% of wildtype levels in cerebrum and cerebellum respectively, glycogen level was not reduced. This confirms previously reported results, in which glycogen in the CNS was not reduced through HSPC gene therapy using solely the GAA sequence (10,16). Surprisingly, although GAA enzyme activity in the GILT-tagged groups in the brain was below detectable enzyme activity levels, lysosomal glycogen was completely reduced to wildtype levels, which was confirmed by near absence of histological PAS staining.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, in our study, although GAA enzyme activity was detectable in the brain of mice in the GAAco group at approximately 11% and 30% of wildtype levels in cerebrum and cerebellum respectively, glycogen level was not reduced. This confirms previously reported results, in which glycogen in the CNS was not reduced through HSPC gene therapy using solely the GAA sequence (10,16). Surprisingly, although GAA enzyme activity in the GILT-tagged groups in the brain was below detectable enzyme activity levels, lysosomal glycogen was completely reduced to wildtype levels, which was confirmed by near absence of histological PAS staining.…”
Section: Discussionsupporting
confidence: 92%
“…3B). Previous studies showed that lentiviral HSPC gene therapy using a GAA transgene effectively reduced heart glycogen levels (10,11,16), but also in our study more than 99% reduction was observed in all the therapeutic groups (except GILTco1-m-ApoE1) at week 16 (Fig. 3C) when compared to Gaa -/mice (441.44 µg glycogen/mg protein; Fig.…”
Section: Genetically Modified Hspcs With Engineered Gaa Clear Glycogen In Heart and Skeletal Musclessupporting
confidence: 78%
See 1 more Smart Citation
“…Numerous pre-clinical studies of HSC-GT have been performed in Pompe disease [ 104 , 105 , 106 , 107 ]. Pompe disease is caused by a deficiency of the acid alpha-glucosidase (GAA) enzyme due to mutations in the GAA gene, resulting in the accumulation of lysosomal glycogen in a variety of cell types.…”
Section: In Vitro Haematopoietic Stem Cell Gene Therapymentioning
confidence: 99%
“…Otherwise, even in the era of ERT, there were still some limitations in treating Pompe disease, such as great expense, immune response due to high amounts of exogenous enzyme, progression of muscle weakness even responding well to ERT initially ( 30 ), limited effects to central nervous system due to blood brain barrier ( 31 ), and white matter abnormalities/ventricular enlargement in brain MRI ( 32 ). Some alternative therapies have been developed, like gene therapy ( 33 , 34 ), enzyme enhancement therapy ( 35 ), and substrate reduction therapy ( 36 ). Further studies were required to determine the benefits of these treatments in decreasing perioperative risks for Pompe disease.…”
Section: Discussionmentioning
confidence: 99%